2017
DOI: 10.1103/physreva.95.010301
|View full text |Cite
|
Sign up to set email alerts
|

Nonlocal advantage of quantum coherence

Abstract: A bipartite state is said to be steerable if and only if it does not have a single system description, i.e., the bipartite state cannot be explained by a local hidden state model. Several steering inequalities have been derived using different local uncertainty relations to verify the ability to control the state of one subsystem by the other party. Here, we derive complementarity relations between coherences measured on mutually unbiased bases using various coherence measures such as the l1-norm, relative ent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
198
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(201 citation statements)
references
References 52 publications
3
198
0
Order By: Relevance
“…They found a Belltype bound for this quantity for all product states A ⊗ B , and showed that the bound is violated for maximally entangled states and a certain choice of observables X and Y. In a similar spirit, the interplay between coherence and quantum steering was investigated in (Mondal and Mukhopadhyay, 2015;Mondal et al, 2017), where steering inequalities for various coherence quantifiers were found, and in , where the maximal coherence of steered states was investigated.…”
Section: E Witnessing Quantum Correlationsmentioning
confidence: 99%
“…They found a Belltype bound for this quantity for all product states A ⊗ B , and showed that the bound is violated for maximally entangled states and a certain choice of observables X and Y. In a similar spirit, the interplay between coherence and quantum steering was investigated in (Mondal and Mukhopadhyay, 2015;Mondal et al, 2017), where steering inequalities for various coherence quantifiers were found, and in , where the maximal coherence of steered states was investigated.…”
Section: E Witnessing Quantum Correlationsmentioning
confidence: 99%
“…Pati et. al [14] showed the existence of reverse uncertainty relations. The reverese uncertainty results means that the product or the sum of the variances of the observables are also bounded from above.…”
Section: Corollarymentioning
confidence: 99%
“…Let, t Alice who hold the first qubit (A), performs a local measurements a i = 1 2 (I 2 + (−1) a σ i ) on her qubit A and informs Bob of her randomly selected observable σ i and the measurement results a ∈ {0, 1}, where σ i being one of the Pauli operators σ x,y,z and I 2 is the 2-dimensional identity operator. By averaging over the three possible measurements of Alice and the corresponding eigenbases choosen by Bob, Mondal et al [22] derived the criterion for achieving the non-local advantage of quantum coherence ( NAQC)C…”
Section: The Non-local Advantage N Lamentioning
confidence: 99%